SOIL DEGRADATION RISK AND HUMAN SECURITY IMPLICATIONS OF LAND USE IN SAMARINDA'S STEEP SLOPES - Muhammad Kimie Aliyev; Talitha Shabrina Fasha; Mardiana Ulan Dari; Alfiansyah; Muhammad Dafi Ramadhan; Arum Sekar Kedhaton; Prince Clinton Immanuel Christian Damanik (Universitas Katolik Indonesia Atma Jaya, 2026)
Soil erosion represents a critical environmental issue that threatens both ecological stability and human security in rapidly developing urban areas of Indonesia. This study aims to assess the soil erosion potential in Air Hitam Subdistrict, Samarinda Ulu, East Kalimantan, through field observation and environmental analysis. The study area is characterized by steep slopes, open-pit mining activities, limited vegetation cover, and high rainfall intensity, which collectively accelerate surface erosion processes and increase landslide potential. The soil type was identified with clay-dominated texture and low permeability, leading to significant surface runoff. Observations revealed clear signs of slope instability, sediment displacement, and exposed subsoil layers, confirming high erosion susceptibility. The degradation of vegetation and soil structure not only increases the likelihood of slope failure but also poses direct risks to surrounding communities, infrastructures, and water systems. To mitigate these impacts, integrated land conservation strategies are recommended, including slope stabilization, drainage improvement, and revegetation using local pioneer species such as Vetiver grass and leguminous cover crops.